Powerful generators of high-voltage pulses with nanosecond fronts - Boyko, N.I. (Електротехніка і електромеханіка, 2018)
Purpose. Purpose of the article is to show the possibility of joint efficient operation of semiconductor switches and spark arresters
in high-powerful high-voltage generators for obtaining nanosecond and shorter pulse fronts on a high-voltage load.
Methodology. The variants of generators of power high-voltage pulses with semiconductor switches in the form of IGBTtransistors, SOS-diodes and spark dischargers as pulse front peaking spark gaps are considered. A scheme is proposed for such a
generator of high-voltage pulses with nanosecond front on the basis of a linear pulsed transformer in the Tesla scheme. Results.
On the complex load of the generator in the form of a serial connection of a gas bubble in water with a discharge in it and a layer
of water under the bubble, voltage pulses with an amplitude of 23 kV and current pulses with an amplitude of 15 A were obtained.
In this case, the pulse front, both voltage and current, on the levels 0.1-0.9, was approximately 10 ns, and the repetition rate of
pulses in the load ranged from 1200 to 5000 pulses per second. Originality. A scheme is proposed for a generator of high-voltage
pulses with a nanosecond front. The difference of the proposed generator with a nanosecond front, high pulse repetition rate,
using its high-voltage and low-voltage circuits in the discharge circuit, is the presence in its composition of a linear pulse
transformer and a system of peaking of pulse front using SOS diodes and spark gaps. Practical value. These generators
considered in this work can find wide application in high-voltage technologies, including decontaminating water treatment, water
purification by electric discharges. Рассмотрены варианты генераторов мощных высоковольтных импульсов с полупроводниковыми коммутаторами в
виде IGBT-транзисторов, SOS-диодов и искровыми разрядниками. Предложена схема такого генератора
высоковольтных импульсов с наносекундным фронтом. Отличием предложенного генератора с наносекундным
фронтом, высокой частотой следования импульсов, с использованием в разрядном контуре его высоковольтных и
низковольтных цепей является наличие в его составе линейного импульсного трансформатора и системы
обострения фронта импульсов с использованием SOS-диодов и искровых разрядников.